Accessible information and inclusive education for students with disabilities in Universitas Airlangga, Indonesia - Artaria, Myrtati Dyah; Suen, Mein-Woei; Alaydrus, Sayf Muhammad (Record and Library Journal, 2025)
Background of the study: Education is a basic human right for all, including persons with disabilities. The right to information for students with disabilities is guaranteed by the national law of the Republic of Indonesia. However, students with disabilities still face discrimination and marginalization on campus that might impede their academic achievement and subjective well-being. Purpose: This study aims to explore information experiences of students with disabilities in Universitas Airlangga, which includes information on university policies, research opportunities, student organizations, and career opportunities. Method: This study employed a mixed-methods approach by conducting in-depth interviews with students with disabilities (n = 5), surveys with non-disabled students (n = 106), and focus group discussions with faculty representatives (n = 10). Findings: This study found that inaccessible information continues to be a problem for students with disabilities. However, some of their non-disabled peers, professors, and staff members have been relatively helpful in navigating their respective campus lives. The commitment to inclusive education is shown by the university and faculties within, but effective and sustainable action is required to tackle these issues. Conclusion: The authors recommend that the university utilize already-existing organizations to conduct workshops and promote inclusive learning on campus.